Experienced versus Inexperienced Interexaminer Reliability on Location and Classification of Myofascial Trigger Point Palpation to Diagnose Lateral Epicondylalgia: An Observational Cross-Sectional Study. (10th January 2016) - Mora-Relucio, Raquel; Núñez-Nagy, Susana; Gallego-Izquierdo, Tomás; Rus, Alma; Plaza-Manzano, Gustavo; Romero-Franco, Natalia; Ferragut-Garcías, Alejandro; Pecos-Martín, Daniel
Abstract : The purpose was to evaluate the interexaminer reliability of experienced and inexperienced examiners on location and classification of myofascial trigger points (MTrPs) in two epicondylar muscles and the association between the MTrP found and the diagnosis of lateral epicondylalgia (LE). Fifty-two pianists (some suffered LE) voluntarily participated in the study. Three physiotherapists (one inexperienced in myofascial pain) examined, located, and marked MTrPs in the extensor carpi radialis brevis (ECRB) and extensor digitorum communis (EDC) muscles. Forearms were photographed and analyzed to establish the degree of agreement on MTrPs diagnosis. Data showed 81.73% and 77.88% of agreement on MTrP classification and 85.58% and 72.12% on MTrP location between the expert evaluators for ECRB and EDC, respectively. The agreement on MTrP classification between experienced and inexperienced examiners was 54.81% and 51.92% for ECRB and 50.00% and 55.77% for EDC. Also, agreement on MTrP location was 54.81% and 60.58% for ECRB and 48.08% and 48.08% for EDC. A strong association was found between presence of relevant MTrPs, LE diagnosis, and forearm pain when the examiners were experts. The analysis of location and classification of MTrPs in the epicondylar muscles through physical examination by experienced evaluators is reliable, reproducible, and suitable for diagnosing LE.